Michael Psellos on literature and art - Michael,Barber, Charles,Papaiōannu, Eustratios (University of Notre Dame Press, 2017)
The ambition of Michael Psellos on Literature and Art is to illustrate an important chapter in the history of Greek literary and art criticism and introduce precisely this aspect of Psellian writing to a wider public.
Literaturverzeichnis Seite 385-403